Good for who? : supermarkets and small farmers in South Africa : a critical review of current approaches to market access for small farmers in developing countries - Van der Heijden, T. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Agricultural Economics)--University of Stellenbosch, 2010.